2019
DOI: 10.1017/s0007114519002708
|View full text |Cite
|
Sign up to set email alerts
|

Maternal high-fat diet triggers metabolic syndrome disorders that are transferred to first and second offspring generations

Abstract: A high-fat (H) diet increases metabolic disorders in offspring. However, there is great variability in the literature regarding the time of exposure, composition of the H diets offered to the genitors and/or offspring and parameters evaluated. Here, we investigated the effect of a H diet subjected to the genitors on different cardio-metabolic parameters on first (F1)- and second (F2)-generation offspring. Female Fischer rats, during mating, gestation and breast-feeding, were subjected to the H diet (G0HF) or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Current evidence has emerged from animal models that offspring exposed to a maternal HFD manifest various components of metabolic syndrome [ 26 , 27 ], including obesity [ 26 ], insulin resistance [ 28 ], liver steatosis [ 29 ], dyslipidemia [ 29 ], and hypertension [ 30 ]. Additionally, maternal HFD may modify the development of the brain, resulting in reduced cognitive development, increased depressive-like and aggressive behaviors, and alteration in feeding habits in the offspring [ 8 ].…”
Section: Maternal High-fat Diet Programs Adult Diseasesmentioning
confidence: 99%
“…Current evidence has emerged from animal models that offspring exposed to a maternal HFD manifest various components of metabolic syndrome [ 26 , 27 ], including obesity [ 26 ], insulin resistance [ 28 ], liver steatosis [ 29 ], dyslipidemia [ 29 ], and hypertension [ 30 ]. Additionally, maternal HFD may modify the development of the brain, resulting in reduced cognitive development, increased depressive-like and aggressive behaviors, and alteration in feeding habits in the offspring [ 8 ].…”
Section: Maternal High-fat Diet Programs Adult Diseasesmentioning
confidence: 99%
“…Different studies pointed towards the possible idea that, across generations, a compromised diet can affect the phenotype and epigenome of the next generation, making them prone to developing metabolic [ 19 ] and even mental illnesses [ 20 ], by epigenetic variations that are subject to variations in diet [ 20 ]. These premises represent a starting point to understand how lifestyle and dietary behaviours during pregnancy can alter an offspring’s health by triggering epigenetic modifications during development.…”
Section: Dohad and Epigenetic Modifications During Developmentmentioning
confidence: 99%
“…Our previous study found that maternal overnutrition was associated with glucose intolerance, insulin intolerance, hyperglycemia and hyperlipidemia in the offspring ( 6 9 ). Increasing studies also indicate that this transgenerational effect even can be transmitted to the next generation ( 10 12 ). However, the underlying mechanisms remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%